The Market of Renewable Energy Sources in the European Union - a Statistical Analysis - Frodyma, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The ongoing dynamic development of civilization has translated into growing demand for energy. The use of traditional energy sources such as coal, oil and natural gas is not only associated with an increase in pollution, but also causes the depletion of natural resources. Renewable sources of energy are an alternative to non-renewable energy sources such as fossil fuels. The main aim of this article is to assess the changes occurring in the market of renewable energy in the European Union. Based on available data, countries were ordered linearly, according to the share of energy from renewable sources they used to produce electricity. Changes in how energy from renewable sources is obtained are discussed. The countries were classified according to how they obtained energy from renewable sources.